The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1021/ol100138k
|View full text |Cite
|
Sign up to set email alerts
|

A Short Biomimetic Synthesis of the Meroterpenoids Guajadial and Psidial A

Abstract: The biosynthesis of the meroterpenoid guajadial was previously hypothesized to occur via a hetero-Diels-Alder reaction between caryophyllene and an o-quinone methide. This hypothesis has been verified via the biomimetic synthesis of guajadial and psidial A in an aqueous three-component coupling reaction, between caryophyllene, benzaldehyde, and diformylphloroglucinol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
86
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(91 citation statements)
references
References 23 publications
(26 reference statements)
5
86
0
Order By: Relevance
“…The absolute configurations of psiguajadials G ( 7 ) and L ( 20 ) were established by analysis of their ECD spectra (see Supplementary S7.59 and S7.67), in which the Cotton effects around at 345 nm (positive for 7 and negative for 20 ) and 284 nm (positive for 7 and negative for 20 ) indicated that the C-1′ configuration of 7 and 20 were R and S , respectively. These assignments were in agreement with the ECD tendencies of those for guajadial ( 19 ) and psidial A ( 18 ) 9, 27 , respectively.
Figure 11Selected NOESY correlations of 7 – 10 .
…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…The absolute configurations of psiguajadials G ( 7 ) and L ( 20 ) were established by analysis of their ECD spectra (see Supplementary S7.59 and S7.67), in which the Cotton effects around at 345 nm (positive for 7 and negative for 20 ) and 284 nm (positive for 7 and negative for 20 ) indicated that the C-1′ configuration of 7 and 20 were R and S , respectively. These assignments were in agreement with the ECD tendencies of those for guajadial ( 19 ) and psidial A ( 18 ) 9, 27 , respectively.
Figure 11Selected NOESY correlations of 7 – 10 .
…”
Section: Resultssupporting
confidence: 78%
“…Psiguajadial G ( 7 ) had the molecular formula C 30 H 34 O 5 as determined by HR-ESI-MS. Its 1D NMR data (Tables 3 and 4) were very similar to those of the synthesized caryophyllane-based meroterpenoid, compound 20 27 , which was isolated as a natural product for the first time in the current study and was given a trivial psiguajadial L. The structural difference between 7 and 20 was being due to the configuration of H-1′, which was designated as α -orientation in 7 by NOE correlations of H 3 -14/H-9′ (13′) and H-1′/H-5 and H-7 α (Fig. 11).…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…The 138 symmetry of the molecule only permitted to propose the structure 139 of the diformylphloroglucinol and although, this pattern is part of 140 many of the macrocarpals, this is the first time that this compound 141 is isolated in the plant kingdom. However, its synthesis has already 142 been described(Lawrence et al, 2010;Modak et al, 2010) and it is 143 worth noting that this compound adds to the very short list of 144 synthetic compounds later found in nature.145 3. Conclusions 146 Supercritical extraction has allowed to obtain an extract rich in 147 non polar compounds.…”
mentioning
confidence: 99%